Waveguide Slot Array Antenna with a Hybrid-Phase Feed for Grating Lobe Reduction - Son Trinh-Van; Sung Chan Song; Seung-Hee Seo; Keum Cheol Hwang (International Journal of Antennas and Propagation)
The design of a 112-element millimeter-wave waveguide slot array antenna to reduce the grating lobe level is presented. A hybrid-phase feeding technique combining a cophase feed and an alternating-phase feed is applied to facilitate the suppression of grating lobes. In addition, a stepped feed waveguide and offset coupling slots aligned in a line are employed to realize a tapered aperture distribution. As a result, grating lobe suppression of 8.1 dB was achieved on the diagonal planes compared to a conventional alternating-phase-fed waveguide slot array antenna. A prototype of the proposed antenna was fabricated and measured. The measured results show that the proposed antenna exhibits a −15 dB reflection bandwidth of 3.4% and an average realized gain of 26.72 dBi within the measured frequency range. Good agreement between the simulated and measured radiation patterns is also observed.